2016
DOI: 10.1074/jbc.m116.734665
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Role of Respiratory Supercomplex Factor Rcf2 and Its N-terminal Homolog Rcf3 in Saccharomyces cerevisiae

Abstract: Edited by Linda SpremulliThe mitochondrial electron transport chain consists of individual protein complexes arranged into large macromolecular structures, termed respiratory chain supercomplexes or respirasomes. In the yeast Saccharomyces cerevisiae, respiratory chain supercomplexes form by association of the bc 1 complex with the cytochrome c oxidase. Formation and maintenance of these assemblies are promoted by specific respiratory supercomplex factors, the Rcf proteins. For these proteins a regulatory func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…Rcf3 may thus function as mediator between respiratory chain III–IV supercomplexes and MICOS. (6) Yil077c assembled into large blue native gel complexes that are characteristic for III–IV supercomplexes (Figures 7A and 7D, right panel), in agreement with the co-purification of Yil077c with Rcf3 (Figure 7C) (Römpler et al., 2016). Tagged Yil077c, named Rci37 (respiratory chain interacting protein of 37 kDa), co-purified subunits of complexes III and IV and additionally the subunits Afg3 and Yta12 of the inner membrane m-AAA protease (Rugarli and Langer, 2012), followed by the prohibitin complex (Figure 7D).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Rcf3 may thus function as mediator between respiratory chain III–IV supercomplexes and MICOS. (6) Yil077c assembled into large blue native gel complexes that are characteristic for III–IV supercomplexes (Figures 7A and 7D, right panel), in agreement with the co-purification of Yil077c with Rcf3 (Figure 7C) (Römpler et al., 2016). Tagged Yil077c, named Rci37 (respiratory chain interacting protein of 37 kDa), co-purified subunits of complexes III and IV and additionally the subunits Afg3 and Yta12 of the inner membrane m-AAA protease (Rugarli and Langer, 2012), followed by the prohibitin complex (Figure 7D).…”
Section: Resultssupporting
confidence: 82%
“…Tmh11 interacts with oligomerization-promoting subunits of MICOS and the F 1 F o -ATP synthase (Arnold et al., 1998, Barbot et al., 2015, Bohnert et al., 2015, Rabl et al., 2009), pointing to an interaction of Tmh11 with a special pool of the MICOS core component Mic10. We found that Rcf3 associates not only with respiratory chain supercomplexes (Römpler et al., 2016) but also with the entire MICOS complex, indicating a role of Rcf3 in linking respiratory chain and the cristae organizing system. Mco10 was found as partner protein of the F 1 F o -ATP synthase, and Coq21 was identified as component of the coenzyme Q biosynthesis cluster.…”
Section: Discussionmentioning
confidence: 96%
“…Formation, maintenance, and regulation of respiratory supercomplexes in S. cerevisiae are promoted by specific factors, the so‐called respiratory supercomplex factor 1 and 2 (Rcf1 and Rcf2) proteins . Rcf2 is a 224‐residue integral membrane protein, located in the mitochondrial inner membrane .…”
Section: Figurementioning
confidence: 99%
“…Formation, maintenance, and regulation of respiratory supercomplexes in S. cerevisiae are promoted by specific factors, the so‐called respiratory supercomplex factor 1 and 2 (Rcf1 and Rcf2) proteins . Rcf2 is a 224‐residue integral membrane protein, located in the mitochondrial inner membrane . Both Rcf1 and Rcf2 have a conserved domain at the N terminus that belongs to the hypoxia‐induced gene 1 family, the function of which might be related to the regulation of supercomplexes in higher eukaryotes as well .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation